The Teaching-Learning of Mathematical Case Problems through Problem Solving Approach for Elementary School Students - Sarjiman Sarjiman (LPPM UNY, 2012)
The aims of the study were to: (1) improve the students' understanding in solving mathematical case problems, (2) improve the students' achievement by problem-solving strategies according to the types of the mathematical case problems, and (3) know the process of teaching-learning about that teaching learning model. The research method used was classroom action research. The study consisted of two cycles.'Each cycle consisted of plan, action, observation, and reflection. The research subjects were 32 students of the fifth grade of the Public Elementary School of Kota Gede V Yogyakarta. The research instruments were a pretest, an achievement test, and an observation sheet. The qualitative data collected through observations and direct interviews were qualitatively analyzed and interpreted, whereas the quantitative data were quantitatively described. The result of thefirst cycle was not satisfactory; the mean score of the posttest was only 61,5, whereas the mean score of the pretest was 41. In the second cycle, the mean score was 78,00, above the stipulated criteria. The teaching-learning process ran as expected. Keywords: mathematical case problems, problem solving, students' achievement